A new species of Ceroplastes (Hemiptera: Coccomorpha: Coccidae) from southwest China evidenced by morphological and molecular data, with a discussion on the variation in the number of clear areas in the C. floridensis species-group - Li, Pengchen; Wang, Xubo (Zootaxa, 2025)
A new species of wax scale, Ceroplastes planoides Li & Wang, sp. nov. (Hemiptera: Coccomorpha: Coccidae), from Yunnan Province, China., is described and illustrated. Phylogenetic analysis based on COI and 28S genes confirms the monophyly of this new species. A key to the currently known species of the genus Ceroplastes in China is provided, along with a discussion on the variation in the number of clear areas within the C. floridensis species group.